Effects of pyrazosulfuron-ethyl on caudal fin regeneration in zebrafish larvae - Chenkai Ge; Zhijun Ye; Weitao Hu; Jingrong Tang; Huimin Li; Fasheng Liu; Xinjun Liao; Jianjun Chen; Shouhua Zhang; Zigang Cao (Ecotoxicology and Environmental Safety)
With the widespread application of pesticides, water pollution problems are becoming more and more serious, which is very likely to cause harm to fish. Lower vertebrates, including fish, have the ability to repair damaged tissues. The spread of pesticides in the water may affect their regeneration process after injury, leading to their death, thereby affecting the survival rate of the population. Therefore, we used zebrafish as a model animal to evaluate the effect of the pesticide pyrazosulfuron-ethyl on caudal fin regeneration in zebrafish larvae. We exposed zebrafish larvae to 0, 5, 15, and 25 mg/L pyrazosulfuron-ethyl at 3 days after caudal fin amputation. It was found that exposure to pyrazosulfuron-ethyl significantly inhibited caudal fin regeneration and affected the behavior of zebrafish larvae. After exposure to pyrazosulfuron-ethyl, proliferating cells decreased and apoptotic cells increased in the caudal fin of zebrafish larvae. Pyrazosulfuron-ethyl exposure resulted in the decreased number of neutrophils and macrophages, and the downregulation of immune related gene expression levels during caudal fin. Using LPS to activate inflammation can effectively rescue the fin regeneration defects induced by pyrazosulfuron-ethyl. However, inhibiting the Notch signaling pathway and inhibiting reactive oxygen cannot rescue the fin regeneration defects induced by pyrazosulfuron-ethyl. Our results indicate that pyrazosulfuron-ethyl can inhibit zebrafish caudal fin regeneration by reducing the number of innate immune cells and affecting the normal process of inflammation, thereby inhibiting caudal fin regeneration. This study expands our understanding of the potential effects of the pesticide pyrazosulfuron-ethyl on injured fish, highlights the link between the immune system and the regeneration process, and demonstrates the potential application of fin regeneration in risk assessments of environmental toxicology to assess drug toxicity.